PLASTIC BLOCK FOR BUILDING CONSTRUCTION MATERIAL - Thanaya, I Nyoman Arya; Mataram, I N. Karnata; Fathan, Muhammad (Journal of Applied Engineering Science, 2024)
Plastic wrap waste increase from time to time. Efforts are needed to utilize them as they are less demanded for recycling by the private sectors in Bali and Indonesia. This paper describe effort to use combination of waste thin plastic wrap as plastic block for wall construction material. The plastic wrap wastes were cut into 5-10 mm size, then they were melted in a hot waste engine oil at 200°C. The mixture was then poured into a metal mold, slightly cooled down and compressed using a compression machine. The mixtures produced was without and with added rice husk ash as filling material. The size of the plastic block was 20×10×8cm. It was found that the densities of the samples were less than 1gram/cm3, the compressive strength can achieve 25kg/cm2, the Porosities were low, ranges from 0.220-0.290%, the Initial Rate of Suctions (IRS) were very low ranges form 0.0004-0.00075 kg/m2.minute, and the and water absorptions were also low (0.02-0.03) %. In general, the compressive strengths were comparable to low quality bricks commonly produced.